Analysis of Convergence Process of Polish Household Food Expenditures - Müller-Frączek, Iwona; Muszyńska, Joanna; Pietrzak, Michał Bernard (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper presents an analysis of expenditure on food of households in Poland in the years 1999–2010. Since their level and dynamics can be used as a measure of well-being of society this process was used to examine internal social convergence of regions, in this case the voivodships. The aim of this paper was to validate the hypothesis about the process for β-convergence in the share of household expenditure on food in total expenditures. The research has allowed the identification of long-term tendency of the level of expenditure on food in Polish households. Based on the analysis of conditional convergence, the article indicates household disposable income as a strong determinant of social convergence process in Poland. For the verification of hypotheses dynamic panel models were applied. The analysis was based on data from the CSO website. All calculations were performed in the Gretl.